PERLINDUNGAN HUKUM KONSUMEN TERHADAP KETERLAMBATAN JADWAL PENERBANGAN BERBASIS BISNIS HIGH PERFOMANCE - Dikha Anugrah (IAIN Syekh Nurjati Cirebon, 2020)
Implementation of the flight can not be done either from the passengers so often, or from the airlines. The delay in flight schedules made by airlines is due to several factors for certain reasons, namely the delay in flight schedules which resulted in the passengers being aggrieved in terms of time, and the long and complex compensation action. The purpose of this study was to analyze the legal consequences of PT Angkasa Pura Husen Sastranegra Bandung Airport related to the delay of flight schedule. The paradigm used in this research is the paradigm of critical theory, with the type of qualitative research and socio-legal approach. The result of the research shows that the policy of Husein Sastranegara Airport in Bandung related to the delay of flight schedule by the airlines by developing good corporate governance structure and system, expressly oblige the airlines to be responsible only in case of delays, the management inform the flight delays, and propose to the Government so that airlines operating in Indonesia are required to make deposits as collateral. While the legal aspect concerning the delay of flight schedule is the enforcement of consumer rights protection through the provision of compensation for the users of air transport services based on Undang-Undang Nomor 8 Tahun 1999 about Consumer Protection as well as legal protection against passengers as consumers who are harmed due to flight delays.